Evaluation of Relationship between Lichen Planus and HCV Antibody - Ali Taghavi Zenouz; Masoumeh Mehdipour; Narges Gholizadeh; Behrooz Naghili; Mohammad Jafari Heydarlou (Tabriz University of Medical Sciences, 2010)
Background and aims. Lichen planus is a relatively common chronic mucocutaneaous disease with an unknown cause, and is considered a manifestation of cell-mediated immune response. Hepatitis C virus (HCV) and its subgroups have been associated with lichen planus in different geographic locations. The present study was undertaken to evaluate the prevalence of HCV antibody in patients with lichen planus in northwest Iran. Materials and methods. This descriptive analytical study included 30 patients with cutaneous lichen planus, 30 patients with oral lichen planus, and 30 healthy individuals as controls. Anti-HCV test was run for all the subjects. Descriptive statistics as well as chi-square test, to compare means in the three study groups, were applied to the data using SPSS 14.0 computer software. Results. Age and sex differences between the groups were not significant. No statistically significant differences were observed in anti-HCV test results between the groups (P = 0.50). Conclusion. No statistically significant relationships were observed between lichen planus and HCV antibody in the studied samples.